2022
DOI: 10.1002/ps.7245
|View full text |Cite
|
Sign up to set email alerts
|

Aphid‐repellent, ladybug‐attraction activities, and binding mechanism of methyl salicylate derivatives containing geraniol moiety

Abstract: BACKGROUND Aphids have been mainly controlled by traditional chemical insecticides, resulting in unamiable risk to the environment over the last decades. Push–pull strategy is regarded as a promising eco‐friendly approach for aphid management through repelling aphid away and attracting their natural enemy. Methyl salicylate (MeSA), one of typical HIPVs (herbivore‐induced plant volatiles), can repel aphids and attract ladybugs. Our previous studies discovered a new lead compound 3e, a salicylate‐substituted car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…The antiviral activity data given in Tables and are the mean ± standard deviation of three replicates. A one-way analysis of variance (ANOVA) followed by Duncan’s test was used for significant differences at P < 0.05, indicating by lower case letters qRT-PCR data were analyzed using GraphPad Prism 8.0.2. Student’s t -test was used for statistical analysis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiviral activity data given in Tables and are the mean ± standard deviation of three replicates. A one-way analysis of variance (ANOVA) followed by Duncan’s test was used for significant differences at P < 0.05, indicating by lower case letters qRT-PCR data were analyzed using GraphPad Prism 8.0.2. Student’s t -test was used for statistical analysis …”
Section: Discussionmentioning
confidence: 99%
“…Food Chem. XXXX, XXX, XXX−XXX indicating by lower case letters46 qRT-PCR data were analyzed using GraphPad Prism 8.0.2. Student's t-test was used for statistical analysis 47.…”
mentioning
confidence: 99%
“…HIPVs play a key role in the tritrophic interactions among plants, herbivores, and their natural enemies, 38 and comprehension of the chemical ecology involving Hippodamia variegata is essential for their efficient use in push–pull strategies developed for pest control 9 . In the current study, the varieties and function of the active volatiles identified in HIPVs from Glycyrrhiza uralensis and Alhagi sparsifolia plants that attracted Hippodamia variegata adults were clarified in the laboratory, and their effects were also evaluated in cotton fields.…”
Section: Discussionmentioning
confidence: 99%
“…The model of ApisOBP9 used for this study was modeled in our previous study. 30 The Surflex docking algorithm in SYBYL 7.3 software was used to perform molecular docking between the ligands and ApisOBP9. 31 Benzyl alcohol, lead compound 5i and compound T9 were employed as representative ligands.…”
Section: Molecular Dockingmentioning
confidence: 99%